2009
DOI: 10.1507/endocrj.k08e-180
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Prevents Congenital Malformations in the Offspring of Diabetic Mice

Abstract: Abstract. It is well known that maternal diabetes causes various congenital malformations. Although there are many reports that folic acid (FA) administration in pregnancy reduces the risk of birth defects including neural tube defects (NTDs), a precise analysis on the preventive effect of FA against diabetic embryopathy has not been done yet. In this study, we analyzed the preventive effects of FA on congenital malformations including NTDs, cardiovascular, and skeletal malformations using a diabetic mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 48 publications
3
49
0
4
Order By: Relevance
“…Interestingly, it has been reported that folic acid reduces the incidence of NTDs in offspring in a mouse model of diabetes (Oyama et al, 2009). To date, however, the interaction between maternal genetic and environmental factors in determining the risk of NTDs has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been reported that folic acid reduces the incidence of NTDs in offspring in a mouse model of diabetes (Oyama et al, 2009). To date, however, the interaction between maternal genetic and environmental factors in determining the risk of NTDs has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The development of almost all organs are affected by maternal diabetes; however, the central nervous system is comparatively more susceptible. [1][2][3] The majority of the diabetic embryopathy studies address mostly visible physical defects, especially neural tube defects (NTDs) and cardiac defects, in developing fetuses which occur in *11% of human cases and in *25% of animals in studies. 2,4 However, many studies have shown that some adult diseases might have their origin in fetal life due to the intrauterine environment during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperglycemia were induced by intraperitoneal injection of a single dose of streptozotocin (STZ, 240 mg/kg body weight, from Sigma chemical Co., St. Louis, Mo) diluted in phosphate-buffered saline pH 7.2 (Oyama, Sugimura, Murase, Uchida, Hayasaka, et al, 2009). After 7 days of injection, the plasma glucose concentration was measured from the tail vein.…”
Section: Experimental Animalsmentioning
confidence: 99%